Ekoteologi Islam dan Hindu pada Alih Fungsi Hutan: Telaah Pemikiran Seyyed Hossein Nasr dan Vandana Shiva - Muizudin, Muizudin; Azmi, Syaiful (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, 2023)
This research examines the eco theological perspective of Seyyed Hossein Nasr and Vandana Shiva, by looking at the relationship between humans, nature and God. The research uses library research. This research shows that eco theological principles are relevant when considering the transfer of forest functions in Indonesia. Forests are seen as a sacred element and a mandate from God to be managed and cared for properly and forest management must prioritize fulfilling the rights of living creatures in forest areas, as well as the eco theological value of cherishing and loving other living creatures. So as a conclusion, Islam and Hinduism, through their theological values, support the preservation of nature.